2010
DOI: 10.1002/ptr.3090
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pomegranate juice on Angiotensin II‐induced hypertension in diabetic wistar rats

Abstract: Acute subcutaneous administration of Angiotensin II (Ang II) causes a rise in blood pressure in diabetic Wistar rats. Diabetes was induced using streptozotocin (70 mg/kg, i.v.). Chronic administration of pomegranate juice (PJ) extract (100 mg/kg and 300 mg/kg; p.o. for 4 weeks) obtained from Punica granatum (punicaceae) fruits reduced the mean arterial blood pressure and vascular reactivity changes to various catecholamines and also reversed the biochemical changes induced by diabetes and Ang II. PJ treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
59
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(62 citation statements)
references
References 34 publications
1
59
0
2
Order By: Relevance
“…72 Other findings reported that pomegranate juice consumption decreased LDL susceptibility to aggregation and retention and increased the activity of serum paraoxonase. 73 Study research suggests that pomegranate juice exert beneficial effects on the evolution of clinical vascular complications, coronary heart disease, and atherogenesis in humans.…”
mentioning
confidence: 95%
“…72 Other findings reported that pomegranate juice consumption decreased LDL susceptibility to aggregation and retention and increased the activity of serum paraoxonase. 73 Study research suggests that pomegranate juice exert beneficial effects on the evolution of clinical vascular complications, coronary heart disease, and atherogenesis in humans.…”
mentioning
confidence: 95%
“…In the case of Moringa oleifera (Chen et al , 2012) and Punica granatum (Mohan et al , 2010), a significant rise in superoxide dismutase activity was observed in the extract treated group, indicating the role of anti-oxidant activity. Similarly an increase in anti-oxidant enzymes such as glutathione peroxidase and catalase in red blood cells was observed after administration of Raphanus sativus extract (Chung et al , 2012) and reduction in aortic superoxide production in the case of Sesamum indicum (Nakano et al , 2002), which was suggested to be the reason for the observed decrease in SBP.…”
Section: Traditional Medicinal Plants With Reported Mode Of Action Wmentioning
confidence: 86%
“…Second, the reduction of ACE activity has been shown in diabetic wistar rats [3] and in humans; even after two weeks administration of PJ [4]. A 36% decrement in serum ACE activity was recorded and a dose-dependent inhibitory effect (31%) of PJ on serum ACE activity was observed also in vitro [4].…”
Section: Dear Editormentioning
confidence: 91%
“…Moreover, it is the responsibility of the attending physician to explain to the hypertensive patient (mainly those with hypertension combined with diabetes, metabolic syndrome or smoking) that this is an adjunctive therapy on top of other no-pharmacological interventions or drug treatments for hypertension [2]. There are no data so far that functional foods compromise the adherence of the patient to antihypertensive drug treatment, if their utility is explained by the physician.Second, the reduction of ACE activity has been shown in diabetic wistar rats [3] and in humans; even after two weeks administration of PJ [4]. A 36% decrement in serum ACE activity was recorded and a dose-dependent inhibitory effect (31%) of PJ on serum ACE activity was observed also in vitro [4].…”
mentioning
confidence: 91%